Radioactivity measurement in glacier and Polar ice-caps: An overview. Issue 1 (March 2020) - Ayoub, Anuor. A.T; Song, Yushou
Abstract: Glacier is an extended mass of ice formed by snow falling and accumulating over the years and moving very slowly either by descending from high mountains, as in valley glaciers or by moving out of accumulation centers, as in glaciers on the continent. Glaciers are a significant source of potable water and plant irrigation, any contamination of this significant source in glaciers due to radionuclides may affect freshwater supplies and livelihoods. It is well known that exposure to ionizing radiation could lead to health hazards and harm to the environment. Therefore, awareness of the distribution and concentrations of natural and artificial radionuclides in the glacier region is crucial, and that is why it provides and clarifies helpful information about radionuclide pollution in the environment. This evaluation gives insights into the overview of the radioactivity of natural and artificial radionuclides in the glacier region (Arctic and Antarctica). These information are crucial for predicting the effects of radionuclide distribution and transport in ecosystems, and can also be an indication of the effects of external human activities in the cold regions.